Examining Average Age at First Marriage within Orthodox Judaism: A Large Community‐Based Study. Issue 3 (18th November 2022) - Sokol, Yosef; Rosenbach, Naomi; Rosensweig, Chayim; Levin, Chynna; Hubner, Shifra; Schechter, Isaac
Abstract: Marriage trends across global communities are influenced by demographic and cultural factors. The marriage age of secular Americans, and multiple religious groups are affected by gender and religious affiliation, but this has not been examined in Orthodox Jewish subcultures. This study explored how gender, cultural affiliation, and shifting cultural affiliation affect the age at first marriage within Orthodox Jewish subcultures differing in openness to Western culture: Yeshiva Orthodoxy and Modern Orthodoxy. Respondents ( n = 3865) provided information about themselves and members of their family but respondents' information was excluded to increase sample representativeness, focusing instead on the 8856 family members. Gender, subcultural affiliation, and individual cultural shifting were all found to affect the age of the first marriage. We interpreted these results in the context of varying cultural beliefs, education, and a perceived surplus of available women. Further examination of related factors may aid community efforts to support individuals in their pursuit of finding marriage partners.